IMPLEMENTASI ANALISIS YURIDIS PERJANJIAN JUAL BELI SAHAM DI PASAR MODAL - Emir Adzan Syazali (Universitas Adiwangsa Jambi, 2020)
Companies need funds as capital in order to run their business. A company can be obtained from various things, one of which is capital or funds from the owner of the company itself. While other ways can be done through buying and selling shares or equity participation in the company. to finance the company itself, for example by purchasing fixed assets, buying materials needed to carry out the production process, or using capital as merchandise and cash reserves. What is the mechanism for buying and selling shares in the capital market and scripless trading in fulfilling the terms of the agreement, analysis of the sale and purchase of BW Book III shares and the sale and purchase agreement in relation to scriptlees trading. The Normative Juridical Method is an approach based on the main legal material by examining theories, concepts, legal principles and statutory regulations, the results of which are buying and selling shares in the capital market according to Law No. 8 of 1995 are carried out in a virtual way. not conventionally or in reality with the era of globalization and technological developments. The scriptless trading system (scriptless trading) in the capital market fulfills the legal requirements of the agreement, the system has fulfilled the legal requirements of the agreement but the buying and selling transaction mechanism is not according to the Civil Code but there are other laws and regulations as the principle of lex specialis de rogate lex generalis